The Role of Teachers in Developing Faith and Devotion in Class III Students of Tunggulwulung 1 State Elementary School, Kec. Pandaan, Kab. Pasuruan - Suci Wulan Dari; Machful Indrakurniawan (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This article was created with the aim of explaining the focus of the research which aims to explore the role of teachers in developing students' faith and devotion at tungulwulung state elementary school 1. This research uses a qualitative descriptive approach, which aims to dig deeper into the methods used by teachers in delivering material. religion and values ​​instilled in the learning process. Through in-depth interviews, direct observation, and documentation studies, researchers collected data regarding the way teachers interact with students and the challenges they face in teaching religious values. The research results show that teachers not only act as teachers, but also as role models who provide examples of ethical and moral behavior. In addition, teachers play a role in creating a learning environment that is conducive to the development of student character. Even though there are challenges such as the diversity of students' backgrounds and lack of support from parents, the role of teachers remains very important in shaping students' religious attitudes and understanding of religious values